Magnetic resonance imaging findings at the first episode of acute optic neuritis - Soelberg, Kerstin; Jarius, Sven; Wildemann, Brigitte (Multiple Sclerosis and Related Disorders, 2018)
Background: Optic neuritis (ON) is a focal demyelinating event, which may evolve into multiple sclerosis (MS). Objective: To study MRI characteristics in the acute phase of the first ON episode. Methods: A prospective population-based study was performed on 31 patients with a first episode of acute ON with a one year follow-up. MRI, clinical evaluation, and detection of aquaporin-4 (AQP4)-IgG and myelin oligodendrocyte glycoprotein (MOG)-IgG was undertaken. For lesion characterization on MRI the optic nerves were divided into three segments: intra-orbital (IO), canalicular (CAN) and chiasmal (CHI). Results: Lesions of the optic nerve were observed in 80.6%(25/31), with IO location in 48%(12/25), CAN in 8% (2/25) and both IO and CAN in 44%(11/25). Patients who converted to MS had lesions located at IO in 77%(10/13), whereas the group with isolated ON had IO and CAN in 73% (8/11), p = 0.003. Brain lesions were observed in 84% (21/25) at onset of ON; 62%(13/25) progressed to MS with more frequent location in brainstem (p = 0.030) and lesions in periventricular areas (p = 0.015). Spinal cord lesions were detected only in patients who progressed to MS (p = 0.002). MOG-IgG was detected in one patient with an optic nerve lesion located at IO and CAN. Serum AQP4-IgG was detected in none. Follow-up MRI showed progression in optic nerve lesions in 55% (11/20) patients. Conclusions: Specific location of optic nerve and brain lesions and the presence of spinal cord lesions in the acute phase of the first ON episode facilitated an MS diagnosis. The extension of optic nerve lesions following ON suggests a long-term progressive degeneration as an important element of ON pathology.